Ethics and planning research - Lo Piccolo, Francesco, 1966-; Thomas, Huw (Ashgate, 2009)
This important and unique book provides a thorough examination of the issues relating to research ethics in planning for an international audience. The authors examine alternative frameworks within which ethical action can be discussed and critically describe the key institutional arrangements surrounding the management of ethical behaviour in research.